GLOBAL TRENDS IN VENTURE CAPITAL IN INNOVATIVE DEVELOPMENT - Aminov Farrux Farxadovich (Journals Park Publishing, 2025)
This work analyzes the impact of venture capital (VC) investments on innovative development on a global scale and the main trends in recent years. The volatility of global VC flows is revealed based on the investment explosion in 2020-2021, the decline in 2022-2023, and the observed investment recovery in the field of generative artificial intelligence in 2025. It will also show the role of promising venture capital areas, in particular in the fields of AI, green technologies, and digital security. During the work, proposals will be developed for developing countries, and practical recommendations will be given on the development of innovative infrastructure and cooperation with international VC funds.
Keywords: Venture capital (VC), Innovative development, Startups, Generative artificial intelligence (AI), Investment trends, Global economy, Technological infrastructure, Mega-round, Unicorn companies, Digital transformation, Green technologies, Developing countries, Capital inflow, VC funds, Innovative ecosystem.